Cross-cultural adaptation and validation of the Karitane Parenting Confidence Scale of maternal confidence assessment for use in Brazil - Lívia W. Pereira; Juliana R. Bernardi; Salete de Matos; Clecio H. da Silva; Marcelo Z. Goldani; Vera L. Bosa (Elsevier, 2018)
Objectives: To transculturally adapt and validate the Karitane Parenting Confidence Scale to the Brazilian Portuguese language and culture and verify the combination of the results with the maternal sociodemographic characteristics. Methodology: This is a validation and transcultural adaptation nestled in a longitudinal and observational study in Porto Alegre, RS, Brazil, assessing mother-infant pairs from different gestational and perinatal environments. The original authors authorized the translation into Brazilian Portuguese, unified version creation, back-translation, analysis by specialists, final version implementation, and acceptance. Cronbach's alpha analysis was performed. The Kruskal-Wallis test with post-hoc Dunn's test was used to compare the study groups. Socioeconomic and demographic characteristics, obtained through a questionnaire in the first 24-48 h of the newborns' life, were associated with maternal results by the Brazilian version of the scale, using Spearman's correlation and Mann-Whitney's test. Results: The sample consisted of 251 postpartum women, with the confidence maternal questionnaire being applied at 15 days postpartum. The median score of the mothers' confidence was 40.00 (37.00-43.00). The protocol obtained a Cronbach's alpha of 0.717. There were significant weak positive correlations between maternal confidence and age (p = 0.013, r = 0.157) and between maternal confidence and schooling (p = 0.048, r = 0.125). Additionally, a significant association was observed between maternal confidence and parity (p = 0.030). Conclusion: The transcultural adaptation and validation of the confidence maternal questionnaire into Brazilian Portuguese language and culture showed good reliability for this sample. The results of its use demonstrated that maternal confidence was associated with schooling, age and parity. Resumo: Objetivos: Adaptar transculturalmente e validar a ferramenta Karitane Parenting Confidence Scale para a língua portuguesa e cultura brasileira além de verificar a associação de seus resultados com as características sociodemográficas maternas. Metodologia: Trata-se da validação e adaptação transcultural aninhada a estudo observacional longitudinal realizado em Porto Alegre (RS), contendo puérperas com diferentes condições gestacionais e perinatais. Os processos ocorreram mediante autorização dos autores originais da escala Karitane Parenting Confidence Scale para a tradução para o português brasileiro, montagem de versão unificada, retradução, análise por experts, aplicação da versão final e validação. Realizou-se a análise Alpha de Cronbach. Para a comparabilidade entre os grupos do estudo utilizou-se o teste Kruskal-Wallis com post hoc de Dunn. As características socioeconômicas e demográficas das puérperas, obtidas através de questionário estruturado nas 24-48 h pós-parto, foram relacionadas com a confiança materna obtida através da aplicação da escala, utilizando-se a correlação de Spearman e o teste Mann-Whitney. Resultados: A amostra foi composta por 251 puérperas, com a aplicação do questionário sobre confiança materna aos 15 dias pós-parto. A mediana da pontuação de confiança materna foi 40,00 [37,00-43,00]. O protocolo obteve valor de Alpha de Cronbach de 0,717. Houve correlações fracas significativas positivas entre confiança e idade materna (p = 0,013; r = 0,157) e entre confiança e escolaridade materna (p = 0,048; r = 0,125). Além disso, houve associação significativa entre a confiança materna e a paridade (p = 0,030). Conclusão: A adaptação transcultural e validação da ferramenta sobre a confiança materna para o português brasileiro mostrou boa confiabilidade. Os resultados de sua aplicação demonstraram que a confiança materna esteve associada à escolaridade, à idade e à paridade. Keywords: Validation studies, Confidence, Postpartum period, Mother-child relations, Palavras-chave: Estudos de validação, Confiança, Período pós-parto, Relações mãe-criança